2019
DOI: 10.1177/0007650319825764
|View full text |Cite
|
Sign up to set email alerts
|

Do Sustainability Rating Schemes Capture Climate Goals?

Abstract: The 2015 Paris Agreement set a global warming limit of 2°C above preindustrial levels. Corporations play an important role in achieving this objective, and methods have recently been developed to map global climate targets to specific industries, and individual corporations within those industries. In this article, we assess whether Sustainability ratings capture corporate performance in meeting the 2°C target. We analyze nine rating schemes used by investors and three commonly used in academic studies. Most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…Many use proprietary metrics and frameworks, or rely on qualitative information (Global Reporting Initiative, 2018). A recent review of corporate environmental performance metrics found inconsistent handling of climate goals, and limited ability to link these metrics to quantitative emissions reductions (Rekker et al, 2019). Some existing approaches use the outputs from a company and use these as a proxy for impact (Vörösmarty et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many use proprietary metrics and frameworks, or rely on qualitative information (Global Reporting Initiative, 2018). A recent review of corporate environmental performance metrics found inconsistent handling of climate goals, and limited ability to link these metrics to quantitative emissions reductions (Rekker et al, 2019). Some existing approaches use the outputs from a company and use these as a proxy for impact (Vörösmarty et al, 2018).…”
mentioning
confidence: 99%
“…A measurement system focused on outcomes (e.g., renewable energy installed, vehicles on the road) does not explicitly measure progress toward all the relevant SDGs in a way that is explicitly linked to the individual SDG indicators (Vörösmarty et al, 2018;Rekker et al, 2019). For example, a company that only measures and reports CO 2 reductions and deployment of renewable energy is tracking its progress toward SDGs 7 (Affordable and Clean Energy), 13 (Climate Action), and 9 (Industry, Innovation, and Infrastructure-which contains CO 2 per unit value as an indicator).…”
mentioning
confidence: 99%
“…None of these studies provide a broad quantitative assessment of progress against established SBTs to date. Such an assessment requires additional data collection, as current sustainability rating schemes do not contain sufficient information to fully determine corporate performance against climate goals [19]. One study in particular calls for greater empirical evidence to evaluate the role of SBTs as an emerging corporate climate governance tool [20].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted in 2015 (EY, 2015), nearly two thirds of investors consider nonfinancial data to be relevant to their decisions. These data generally come from SRAs, whose main mission is to measure and compare companies according to their performance and ESG risks (Avetisyan & Hockerts, 2017; Escrig‐Olmedo, Fernández‐Izquierdo, Ferrero‐Ferrero, Rivera‐Lirio, & Muñoz‐Torres, 2019; Rekker, Humphrey, & O'Brien, 2019). Nevertheless, the methods used by SRAs and the challenges involved in assessing sustainability risks remain poorly studied in the literature (Scalet & Kelly, 2010; Stubbs & Rogers, 2013; SustainAbility, 2018).…”
Section: Introductionmentioning
confidence: 99%